Renal atrophy after stereotactic body radiotherapy for renal cell carcinoma. Issue 1 (December 2016) - Yamamoto, Takaya; Kadoya, Noriyuki; Takeda, Ken; Matsushita, Haruo; Umezawa, Rei; Sato, Kiyokazu; Kubozono, Masaki; Ito, Kengo; Ishikawa, Yojiro; Kozumi, Maiko; Takahashi, Noriyoshi; Katagiri, Yu; et al.
Abstract Background Renal atrophy is observed in an irradiated kidney. The aim of this study was to determine dose-volume histogram parameters and other factors that predict renal atrophy after 10-fraction stereotactic body radiotherapy (SBRT) for primary renal cell carcinoma (RCC). Methods A total of 14 patients (11 males, 3 females) who received SBRT for RCC at Tohoku University Hospital between April 2010 and February 2014 were analyzed. The median serum creatinine level was 1.1 mg/dl and two patients had a single kidney. Nine patients were implanted with fiducial markers. The median tumor diameter was 30 mm. SBRT was delivered at 70 Gy in 10 fractions for 7 tumors, at 60 Gy in 10 fractions for 2 tumors, and at 50 Gy in 10 fractions for 5 tumors with 6 and/or 15 MV X-ray using 5 to 8 multi-static beams. Renal atrophy was assessed using post-SBRT CT images after 12–24 months intervals. Correlations were examined by Spearman rank correlation analysis. Differences between two groups were evaluated by the Mann-Whitney test, and pairwise comparisons were made by the Wilcoxon signed-rank test. Results The median tumor volume shrunk from 14.8 cc to 10.6 cc (p = 0.12), and the median irradiated kidney volume changed from 160.4 cc to 137.1 cc (p < .01). The median peak creatinine level was 1.6 mg/dl after treatment (p < .01). Percentage volumes of the irradiated kidney receiving at least 10 Gy (V10, p = 0.03), V20 (p < .01), V30 (p < .01), V40 (p = 0.01), mean irradiated kidney dose (p < .01), and magnitude of overlap between PTV and kidney volume (p = 0.03) were significantly correlated with post-treatment irradiated kidney volume in percent, and V20 -V30 had strong correlation (r < −0.70, p < .01). Patients with implanted fiducial markers showed a significantly lower ratio of renal atrophy (p = 0.02). Conclusions Significant renal atrophic change was observed. Dose distribution of SBRT at 20–30 Gy had a strong correlation with renal atrophy when irradiation was performed in 10 fractions.